Regulation of Intertidal Microphytobenthos Photosynthesis Over a Diel Emersion Period Is Strongly Affected by Diatom Migration Patterns - Cartaxana, Paulo; Cruz, Sónia; Gameiro, Carla; Kühl, Michael (Frontiers in Microbiology, 2016)
Changes in biomass and photosynthesis of a diatom-dominated microphytobenthos (MPB) intertidal community were studied over a diel emersion period using a combination of O2 and scalar irradiance microprofiling, variable chlorophyll (Chl) fluorescence, and pigment analysis. The MPB biomass in the photic zone (0–0.5 mm) of the sediment exposed to low irradiance (150 μmol photons m–2 s–1) showed a >2-fold increase during the first hours of the emersion period, reaching >0.2 mg Chl a cm-3. Concentrations of Chl a started to decrease half-way through the emersion period, almost 2 h before tidal inundation. Similarly, O2 concentrations and volumetric gross photosynthesis in the photic zone increased during the first half of the emersion period and then decreased towards the timing of incoming tide/darkness. The results suggest that intertidal MPB community-level photosynthesis is mainly controlled by changes in the productive biomass of the photic zone determined by cell migration. A diel pattern in the photosynthesis vs. irradiance parameters α (photosynthetic efficiency at limiting irradiance) and ETRmax (photosynthetic capacity at saturating irradiance) was also observed, suggesting photoacclimation of MPB photosynthesis. Under high light exposure (2000 μmol photons m–2 s–1), lower α, ETRmax and sediment O2 concentrations were observed when cell migration was inhibited with the diatom motility inhibitor latrunculin A (Lat A), showing that migration is also used by MPB to maximize photosynthesis by reducing exposure to potentially photoinhibitory light levels. A higher de-epoxidation state in sediment treated with Lat A indicates that the involvement of the xanthophyll cycle in physiological photoprotection is more relevant in MPB when cells are inhibited from migrating. In the studied diatom-dominated MPB intertidal community, cell migration seems to be the key factor regulating photosynthesis over a diel emersion period and upon changes in light exposure.